THE EFFECT OF WORK PLACEMENT, WORK ENVIRONMENT, WORK COMMITMENT ON IMPROVING EMPLOYEE PERFORMANCE WITH FACILITIES AN INFRASTRUCTURE AS INTERVENING VARIABLES AT THE OFFICE OF THE PORT MASTER AND CLASS I PORT AUTHORITY OF TANJUNG BALAI KARIMUN - Armen; Bambang Satriawan; Muammar Khaddafi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study examines the Influence of Job Placement, Work Environment, Work Commitment on Improving Employee Performance with Facilities and Infrastructure as Intervening Variables at the Harbormaster and Port Authority Office Class I Tanjung Balai Karimun. This study uses a quantitative approach based on statistical information. Data collection techniques use variable measurement using questionnaire instruments. Data analysis techniques in this study use Partial Least Square (PLS). The results of the study Job Placement has a positive but insignificant effect on the Facilities and Infrastructure variable. Work Environment has a positive but significant effect on the Facilities and Infrastructure variable. Work Commitment has a positive but significant effect on the Facilities and Infrastructure variable. Facilities and Infrastructure have a positive but significant effect on the Employee Performance variable. Job Placement has a positive but significant effect on the Employee Performance variable. Work Environment has a positive but significant effect on the Employee Performance variable. Work Commitment has a positive but significant effect on the Employee Performance variable. Facilities and Infrastructure have a positive but insignificant effect in mediating Job Placement on Employee Performance. Facilities and Infrastructure have a positive and significant effect in mediating the Work Environment on Employee Performance. Facilities and Infrastructure have a positive and significant effect in mediating Work Commitment on Employee Performance